Decision Support System for Prioritizing Building Material Restocking Using the Simple Additive Weighting Method at Sinar Mas Putra Building Store - Iftikhar Rizqullah; Eko Darmanto; Arif Setiawan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Inventory management plays a vital role in maintaining operational efficiency and customer satisfaction in building material stores.Sinar Mas Putra Building Store, Jepara, experiences difficulties in determining restocking priorities because inventory decisions are primarily based on estimation and personal experience, which may result in stock shortages or overstock conditions.This study aims to develop a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to support objective restocking decisions.The system evaluates products based on five criteria: stock quantity, sales level, product price, lead time, and demand level.This study adopted the Waterfall software development model, while data were collected through observation, interviews, and documentation. The proposed system was implemented as a web-based application and validated using Black Box Testing to ensure that all functional requirements were fulfilled.The results demonstrate that the proposed DSS successfully generates systematic and objective restocking priority recommendations by integrating multiple evaluation criteria into a single decision-making process.Compared with conventional manual practices, the proposed system improves the consistency, accuracy, and efficiency of inventory decision-making.Therefore, the proposed system provides practical support for inventory management and contributes to more effective and reliable restocking decisions at Sinar Mas Putra Building Store.